Evaluasi Manajemen Operasional Pada PT Aneka Gas Industri - Khoiriyah, Laila; Novia, Fina; W, Tri Ngudi (Universitas Pahlawan Tuanku Tambusai, 2024)
This study examines the implementation of operational management at PT Aneka Gas Industri (AGI), a local company in Batam City. The results show that PT AGI has implemented various aspects of operational management, including quality management through ISO certification, annual planning, efficient supply chain management between the company, suppliers and consumers, as well as strategic location strategies. This research focuses on qualitative analysis using direct interviews with the company's HR/HSE without using samples, making PT AGI a single case in the operational management analysis.